Potentially zoonotic gastrointestinal parasites of dogs in Lunugala Tea estate community in Central Sri Lanka - K. O. Bandaranayaka; R. P. V. J. Rajapakse; R.S. Rajakaruna (Ceylon Journal of Science, 2019)
Coprological examination of gastrointestinal (GI) parasites and their life stages in humans and dogs and in soil was carried out in a low income tea estate community in the Central Province. This community has limited access to public health facilities and veterinary services and lives in close contact with free roaming dogs. Parasites in faeces were isolated and identified morphologically and morphometrically using microscopical methods, followed by molecular confirmation of selected protozoans. Soil samples collected from the neighbourhood were analyzed for soil inhabiting parasitic stages. Of the 50 dogs examined, 86.0% was infected with one or more parasites with a significantly higher number of dogs having mixed infections than single infections. Dogs harboured 13 GI parasites, of which nine were known zoonotic species: Toxocara canis, Strongyloides sp., Entamoeba coli, hookworm, Trichuris sp., Giardia duodenalis, Spirocerca lupi, Toxascaris sp., and Taenia sp. Additionally Entamoeba histolytica, coccidia, unidentified trematodes and cestodes were also found in dogs. Six types of GI parasites were identified in humans, of these four types, E. coli, G. duodenalis, Strongyloides sp. and Blastocystis sp. were potentially acquired from animals. A total of 16 soil samples were analyzed, of which 44.4% were carrying infective nematode L3 larvae and eggs, cysts of E. coli and eggs of T. canis all of which were zoonotic. High prevalence of zoonotic infections in dog population and in soil poses a serious health threat to the community. Results highlight the importance of regular deworming of both humans and dogs and reducing environmental contamination, a One Health approach incorporating veterinary and public health interventions in the surveillance and management of zoonoses.